FTIR and rheology study of alginate samples: Effect of radiation. (January 2023) - Mollah, M.Z.I.; Faruque, M.R.I.; Bradley, D.A.; Khandaker, M.U.; Assaf, Saphwan Al
Abstract: Two well characterised alginate samples with high and low M/G ratio were subjected to radiation decontamination dose at 15 kGy. Subsequently, a number of techniques were used to determine the effect of radiation on the gelling properties. These techniques include: (GPC-MALLS) gel permeation chromatography linked to a multi-angle laser light scattering and refractive index detector for the determination of molecular weight and distribution. To observe the mechanics, the deformation with flow of α-β alginates rheological measurements in the dynamic oscillation modes, and distinguish the functional group of the samples along with identifying the M/G ratio for quantitative determination of mannuronic and guluronic acid, the FTIR techniques were performed respectively. The results showed clear reduction in the molecular weight following irradiation which was also accompanied by a loss of the gelling properties as well as clear reduction intensity of FTIR peak at 1080 -1400 cm −1 for carboxylic group, OH-bonding obtained at 1030 cm −1 (1026 and 1028 cm −1 ) while the weak signal and skeletal region is attributed at >2800 and < 700 cm −1 respectively. A sample (n = 1; H120L) is homopolyguluronic enriched (820 cm −1 in fingerprint region) with small amount of mannuronic acid fraction. Sample (n = 2; LFR-5/60) is heteropolyguluronic acid enriched in presence of tiny amount guluronic acid (814 cm −1 peak) i.e. comparatively high G to M in this fraction but %G is lower than n = 1. The rheological parameter storage modulus (G′) and loss modulus (G " ) were noticed higher with the constant frequency mode, a solid-like nature gels was obtained with increasing the frequency in a certain time of relaxation. The gelling properties of the samples calculated is M/G < 1 which able to make hard and rigid gel. Thus, radiation effects for rheology and FTIR in case of functional group distribution was significant. Highlights: Effect of γ-radiation was significant, the role of CaCl2 was responsive in sample. The FTIR revealed the spectrum difference with control and irradiated. The salt and protein (GDL) performed crossover point remarkably. Increasing frequency stated gradual increase of storage and los modulus but G'>G″